Resilience of The Sumberwuluh Village Community in Facing Semeru Disaster - Al Jundi, Ulil Albab Abdullah; Nabila, Rafa; Fahima, Tiza; Citraningrum, Andika (Fakultas Teknik Universitas Brawijaya, 2024)
Mount Semeru eruption in December 2021 caused fatalities, injuries, as well as housing and economic losses for the people of Sumberwuluh Village, Lumajang, East Java, Indonesia. As one of the areas through which the Mount Semeru river basin passes, cold lava floods are an annual disaster in Sumberwuluh when the rainy season comes. This research was done through direct field observations and interviews, supported by secondary data sources in the form of literature, to examine the Sumberwuluh community's resiliency in disasters, emphasizing the economic and social aspects. The research findings suggest that the Sumberwuluh people successfully adapted to economic changes and developed social cooperation to survive. Economic resilience involves changing livelihoods to become sand and stone miners, as well as efforts to find alternative sources of income. On the other hand, social resilience includes coordination and cooperation between residents and forming groups as a preventive measure against disasters. This resiliency is built through the community's collective efforts to overcome the economic crisis and face the disaster threat.